ULTRASOUND FEATURES OF ADENOMYOSIS AND JUNCTIONAL ZONE INVOLVEMENT IN WOMEN WITH PRIMARY INFERTILITY AT DR. SAIFUL ANWAR HOSPITAL - Nurdila, Annisa Safira; Nurdiana, Farah (Department of Radiology, Medical Faculty, University of Brawijaya, 2026)
Adenomyosis is increasingly recognized as a potential contributor to infertility in women of reproductive age. The present research focused on identifying the sonographic patterns of adenomyosis and the involvement of the junctional zone among women diagnosed with primary infertility at Dr. Saiful Anwar General Hospital. A descriptive-correlational design was used, involving 49 women with confirmed adenomyosis on ultrasound and a documented history of primary infertility. Data on lesion morphology, junctional zone thickness, and infertility duration were analyzed. The most common lesion types were diffuse and focal posterior, each found in 22 participants, while five had focal anterior lesions. Mean infertility duration across all groups was approximately eight years, with no significant difference between lesion types. Statistical analysis revealed significant association between lesion morphology and junctional zone involvement. These findings suggest that both focal and diffuse forms of adenomyosis are linked to prolonged infertility, regardless of lesion location, highlighting the importance of junctional zone assessment during infertility evaluations.